Discovery of a new supernova remnant G21.8−3.0. Issue 2 (2nd March 2020) - Gao, X Y; Reich, P; Reich, W; Hou, L G; Han, J L
ABSTRACT: Sensitive radio continuum surveys of the Galactic plane are ideal for discovering new supernova remnants (SNRs). From the Sino-German λ6-cm polarization survey of the Galactic plane, an extended shell-like structure has been found at ℓ = 21^°_. 8, b = −3^°_. 0, which has a size of about 1°. New observations were made with the Effelsberg 100-m radio telescope at λ11 cm to estimate the source spectrum, together with Urumqi λ6-cm and Effelsberg λ21-cm data. The spectral index of G21.8−3.0 was found to be α = −0.72 ± 0.16. Polarized emission was mostly detected in the eastern half of G21.8−3.0 at both λ6 and λ11 cm. These properties, together with the Hα filament along its northern periphery and the lack of infrared emission, indicate that the emission is non-thermal, as is usual in shell-type SNRs.